A história em ponto pequeno: prática votiva e culto santoral nas Minas (Sécs. XVIII-XIX) - Weslley Fernandes Rodrigues (2012)
Our research focuses on the votive practice analyzed by the painted ex-voto [Latin expression] produced during the eighteenth and nineteenth century in Minas Gerais-Brazil. The ex-voto can be an object, monument, action, sacrifice offered to the deity or to the supernatural beings in recognition of a favor received. We define the painted ex-voto as votive tablets generally in small size offered to Christ, to the Virgin Mary or to a saint, made in remembrance of received favors and also to fulfill a vow. This religious manifestation, whose roots lie in polytheistic cultures, started to be developed in Christianity with the cult of saints in the early centuries of the Christian era. The votive practice thus comprises the both moments: the vows and the realization of a promise through the ex-votos. We would like to emphasize the association between the votive practice and the cult of saints. The appeal to the saints as intermediaries of individuals with God in their earthly demands was reaffirmed and valued by the decrees of the Council of Trent and all the religious literature produced in this period, as several books about the lives of saints written in the Modern Age. This bibliography created patterns of behaviors that Christians should follow and also demonstrated the ability of these to intercede with God. Therefore, the votive practice was in accordance with the Trent precepts as it was related to belief in miracles reaffirmed by the Church throughout its history.